Dual-Ignition Musket Locks Including a Matchlock — a Note on their Design and Utility. (April 2014) - Williams, David; Godwin, Brian
<x content-type="archive" xml:space="preserve">Abstract</x> A review is presented of dual-ignition musket locks, including a matchlock, to identify the key design variants and their subtleties, and to initiate a discussion on their utility.